The Meanings of The Philosophy of Symbol of The Patuaekkon Tradition In The Mandailing Muslim Bataknesse Community on The Northern Border of West Sumatra - Fitri Mawaddah (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2021)
This article aims to describe the meaning of symbolic philosophy contained in patuaekkon tradition at the wedding of Mandailing Batak Muslim community in Kampung Harapan Village, Pasaman Regency. This research article uses the field research method, in which the researcher collects data directly at the research location to strengthen the results of the philosophical meaning contained in patuaekkon tradition with a descriptive approach. The results of this study indicate that the meaning of symbolic philosophy of patuaekkon tradition consists of water symbolizing purity, kaffir lime symbolizing cleanliness, silunjuang leaves symbolizing self-adjustment, midrib leaf of banana stem and miracle leaves symbolizing peace and tranquility, nacar symbolizing the process of life's journey, ulos symbolizing blessing and affection, onang-onang song as an expression of joy, praise, hope, advice, and prayer. Poda has a meaning as advice in social life, ways to find a good and right livelihood, and habits in life.Artikel ini bertujuan untuk menguraikan makna filosofi simboik yang terkandung dalam tradisi patuakkon pada pernikahan komunitas Muslim Batak Mandailing Perbatasan utara di Kampung Harapan Kabupaten Pasaman. Penelitian artikel ini menggunakan metode field reasearch, dimana peneliti mengumpulkan data-data secara langsung di lokasi penelitian untuk memperkuat hasil makna filosofi yang terkandung dalam tradisi patuaekkon dengan pendekatan deskriptif. Hasil penelitian ini menunjukkan bahwa makna filosofi simbolik tradisi patuaekkon terdiri dari air melambangkan kesucian, jeruk purut melambangkan kebersihan, daun silunjuang melambangkan penyusaian diri, pelepah batang pisang dan daun cocor bebek melambangkan kedamaian dan ketentraman, nacar melambangkan proses perjalanan hidup, ulos sebagai makna restu dan kasih sayang, lagu onang-onang sebagai ungkapan kegembiraan, pujian, harapan, nasehat, dan do’a, poda memiliki makna sebagai nasehat dalam berkehidupan sosial, cara-cara mencari penghidupan yang baik dan benar, dan kebiasaan yang dilakukan dalam kehidupan